Frontispiece: Amorphous Ionic Polymers with Color‐Tunable Ultralong Organic Phosphorescence. Issue 52 (17th December 2019) - Wang, He; Shi, Huifang; Ye, Wenpeng; Yao, Xiaokang; Wang, Qian; Dong, Chaomin; Jia, Wenyong; Ma, Huili; Cai, Suzhi; Huang, Kaiwei; Fu, Lishun; Zhang, Yanyun; et al.
Abstract : Phosphorescent Materials Amorphous polymers showing ultralong organic phosphorescence are presented by Z. An et al. in their Communication on page 18776 . The emission color could be manipulated from blue to red over the entire visible region.